2017
DOI: 10.25186/cs.v12i4.1359
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da distribuição de árvores sobre atributos do solo em cafeeiro sombreado

Abstract: Objetivou-se com esse trabalho avaliar o efeito da distribuição espacial de árvores (Anadenanthera falcata, Albizia polycephala e Cassia grandis) em cultivo de cafeeiro sombreado (Coffea arabica cv. Obatâ), sobre a resistência mecânica, umidade e propriedades químicas do solo. O delineamento experimental foi o de blocos casualizados com quatro repetições, em esquema fatorial 4x2. O primeiro fator foi a localização dos pontos de amostragem do solo no cafezal sombreado, determinados por dois pontos na mesma linh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…According to Morais et al [26], hydric stress associated with high temperature can quicken cherries maturation. However, Morinigo [27], working in the same site, period, and plots, did not find any difference in soil moisture in 0,0-20 and 0,20-0,40 m depths. Treatments also did not affect Brix degree of ripe cherries.…”
Section: Resultsmentioning
confidence: 72%
“…According to Morais et al [26], hydric stress associated with high temperature can quicken cherries maturation. However, Morinigo [27], working in the same site, period, and plots, did not find any difference in soil moisture in 0,0-20 and 0,20-0,40 m depths. Treatments also did not affect Brix degree of ripe cherries.…”
Section: Resultsmentioning
confidence: 72%
“…The authors found no difference in soil K + content in the evaluated cropping systems. Morinigo et al (2017) found, in shaded coffee cultivation, that the spatial distribution of Fabaceae (Anadenanthera falcata, Albizia polycephala and Cassia grandis) trees, located 1 and 6 meters away from the coffee tree, did not alter soil chemical attributes, organic matter, P, K and Ca, at a depth of 0-0.2m.…”
Section: Resultsmentioning
confidence: 90%
“…Coffee is the most popular and most consumed beverage in the world (Souza et al, 2017). Brazil is the world's leading coffee producer and exporter and, in the country, coffee is predominantly grown in monoculture (Morinigo et al, 2017;Souza et al, 2017;Conab, 2019) However, it is very common in some producing regions of the world, such as Colombia and Central American countries, to grow shaded coffee trees, as a function of the origin of the coffee tree in moderately shaded understory environments, and once the crop is not tolerant to high temperatures (Jaramillo-Botero;Martinez;Santos, 2006;Valentini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%